Berbagi Pengetahuan Sebagai Mediator Pengaruh Persepsi Dukungan Organisasi terhadap Perilaku Inovasi UMKM Batik Jember - Setyanti, Sri Wahyu Lelly Hana; Nilasari, Faris Septia; Prajitiasari, Emma Desia; Sudarsih, Sudarsih (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim: To test how the role of knowledge sharing as a mediator influences perceptions of organizational support on the innovation behaviour of Batik SMEs in Jember Regency Design/ Method/ Approach: The research method uses quantitative data by using the MSI (Successive Interval Method) data transformation method with path analysis techniques (path analysis) Research Findings: significant influence of perceived organizational support variables on innovative behaviour, both directly and indirectly, through knowledge sharing variables. The direct effect coefficient is 0.564, while the indirect effect coefficient is 0.247. This shows that the three hypotheses prepared are acceptable because they are proven significant. Theoretical Contribution/ Originality: The conceptual framework proposed in this model is an adaptation and synthesis of various previous research findings. Therefore this study conceptually emerges a new model in which knowledge sharing is treated as a mediating variable in mediating the effect of perceived organizational support on innovation behaviour. Practitionel/Policy implication : For MSME managers and related agency policymakers, find out how the role of knowledge-sharing mediator variables mediates the influence of perceptions of organizational support to take appropriate actions to increase the innovative behaviour of Batik MSMEs. Through this research, two important things will be obtained. They were first able to find out how to implement knowledge sharing in Batik MSMEs, which have competency advantages to increase innovative behaviour. Second, know how to increase the perception of organizational support by implementing knowledge-sharing practices in Batik SMEs. Research Limitations: The selection of research variables led to sampling criteria adjusted to research needs, so not all batik UMKM employees in Jember Regency became the research sample. Keywords: Knowledge Sharing, Perceived Organizational Support, Innovative Behavior, MSMEs